Potential Antifungal of Merang Padi Extract (Oryza sativa) Against Fungal Growth - Masniah Masniah; Ahmad Purnawarman Faisal (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Merang padi is a traditional medicine that comes from natural ingredients, namely plants. However, there has not been much research on the activity of rice straw extract (Oryza sativa) being explored and researched. The aim of this research was to determine the yield of extracts and the number of antifungal isolates in inhibiting fungal growth and their potential as antifungals against Candida albicans and Aspergillus fumigatus fungi. This research uses experimental research with a quantitative approach carried out through laboratory tests. The design used was a Completely Randomized Design (CRD) which was grouped into 6 treatment groups, namely 4 groups of rice straw extract and 2 control groups which were repeated for each treatment 4 times. The treatment group consisted of P1 with rice straw extract with a concentration of 20,000 ppm, P2 with rice straw extract with a concentration of 40,000 ppm, P3 with rice straw extract with a concentration of 60,000 ppm and P4 with rice straw extract with a concentration of 80,000 ppm. Meanwhile, the control group, namely P0 as a negative control, namely NaCl 0.9% and P5 as a positive control, namely Nystatin 100,000 IU. The research sample was rice straw from rice plants that had been identified and then weighed. Data analysis used one way ANOVA SPSS version 20. If there were differences then a further test was carried out, namely the Honest Significant Difference Test (BNJ) to see the differences between each treatment based on the coefficient of diversity (KK) value obtained at the 5% test level. The results of tests that have been carried out show that the n-hexane fraction of rice straw has no antifungal activity, while the ethyl acetate and n-butanol fractions have antifungal activity. The concentration of ethyl acetate in this study was greater than the other compounds. Keywords : Candida albicus, merang padi, mushrooms, oryza sativa